DEVELOPMENT AND EVALUATION OF MICROEMULSION FORMULATIONS OF BIFONAZOLE - Islam, Md. Shahidul; Mojumder, Tanjum Jahan; Nawrin, Farjana (Universal Journal of Pharmaceutical Research, 2023)
Aim and objective: The purpose of this study was to develop microemulsion formulations for topical delivery of bifonazole with an objective to increase the solubility of the drug. Methods: Total 5 microemulsion formulations were developed using water titration method. Capmul Pg-12 (oil), Tween-80: (surfactant) and Propylene glycol (co-surfactant) were used in different ratio based on the solubility and emulsification efficiency. Prepared formulations were evaluated on different parameters like transmittance (%), pH, refractive index, viscosity, drug content, solubility, and in-vitro release study Franz diffusion cell. Ternary phase diagram was prepared using oil (Capmul Pg-12), surfactant (Tween 80), co-surfactant (Propylene glycol) in different ratio Results: The % transmission was found to be in the range of 98.47±0.09 to 99.2±0.08%, the pH value was found to be in the range of 3.34±0.08 to 4.02±0.09, refractive index in the range of 1.3418±0.016 to 1.3818±0.004, drug content was found to be in the range of 98.47± 0.08 to 99.62±0.02 %, viscosity was found to be in the range of 65.23±2.1 to 71.56±5.77%. It was seen that after 4 hours of diffusion, the drug released from the formulation ME5 faster and more than that of the other ratios i.e., 91.2±0.06%. It was observed that drug release was governed by the diffusion process. Conclusion: On the basis of different evaluation parameters microemulsion formulations of batch ME5 were found to be the best. Present study concludes successful delivery of Bifonazole by the means of microemulsion formulations Peer Review History: Received: 4 April 2023; Revised: 10 May; Accepted: 26 June 2023; Available online: 15 July 2023 Academic Editor: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Reviewers: Rola Jadallah, Arab American University, Palestine, rola@aauj.edu Dr. Taiwo O Elufioye, University of Ibadan, Nigeria, toonitaiwo@yahoo.com